An analysis of the immune compartment within bovine adipose tissue. (November 2019) - Bentley, Eleanor G.; Pugh, Glesni; Gledhill, Laura R.; Flynn, Robin J.
Abstract: Adipose tissue (AT) has wide functions as an active endocrine organ acting as a site of nutrient storage and thermogenesis. Recently it has been identified as having a key role in murine and human immunity and inflammation. Type 1 or type 2 immune responses and their respective cytokines have been linked to white or brown AT, respectively. Most dramatic is the involvement of type-2 innate lymphoid cells (ILC2s) in stimulating eosinophil recruitment via interleukin (IL)-13 which in turn stimulates alternative macrophage activation via IL-4/IL-13. Recruited leukocytes are capable of influencing the cellular composition and function of adipose tissue and present a route to combat human obesity, however these processes are poorly understood in ruminants. Here we have characterised the resident leukocytes populations within bovine mesenteric AT (MAT) and subcutaneous AT (SAT), compared with the corresponding mesenteric lymph node (MLN). Concurring with related studies, we find bovine AT has its own resident leukocyte populations where eosinophils and neutrophils dominate. Importantly the proportion of eosinophils or neutrophils corresponded to the adipocyte size found in both depots. Further exploration of this area may have important implications on the food production industry or could be applied to improve the course of pathogenesis during disease. Highlights: Bovine adipose tissue contain smaller leukocyte pools than those present in mesenteric lymph nodes. All leukocytes are present in the adipose tissues sampled. Eosinophils dominate in terms of absolute and proportional values. Adipose tissues are cytokine competent.